2021
DOI: 10.1080/19490976.2020.1865706
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides uniformis combined with fiber amplifies metabolic and immune benefits in obese mice

Abstract: Gut microbiota represents a therapeutic target for obesity. We hypothesize that B. uniformis CECT 7771 combined with wheat bran extract (WBE), its preferred carbon source, may exert superior anti-obesity effects. We performed a 17-week intervention in diet-induced obese mice receiving either B. uniformis , WBE, or their combination to identify interactions and independent actions on metabolism and immunity. B. uniformis combined with WBE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 67 publications
2
84
0
Order By: Relevance
“…These results suggested that the decrease in gut microflora which produced SCFAs may be responsible for the poor outcome of HTGAP patients. Some Bacteroides species within the family Bacteroidaceae , including Bacteroides ovatus , Bacteroides xylanisolvens , and Bacteroides uniformis , were essential species to induce the production of gut IgA, which acted as a protective factor for maintaining the stability of the intestinal environment by limiting the bacteria and endotoxin invasive intestinal epithelial cells, facilitating bacterial clearance, and regulating bacterial colonization [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the decrease in gut microflora which produced SCFAs may be responsible for the poor outcome of HTGAP patients. Some Bacteroides species within the family Bacteroidaceae , including Bacteroides ovatus , Bacteroides xylanisolvens , and Bacteroides uniformis , were essential species to induce the production of gut IgA, which acted as a protective factor for maintaining the stability of the intestinal environment by limiting the bacteria and endotoxin invasive intestinal epithelial cells, facilitating bacterial clearance, and regulating bacterial colonization [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of different Bacteroides species in alleviating diseases have been demonstrated in a series of studies, including inhibiting tumor [13] , protecting against colitis [14] , alleviating obesity [15] , preventing atherosclerosis [16] , etc. Interestingly, different species of Bacteroides regulated the human health and diseases through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, obesity-related NAFLD patients, especially children, usually have a low adherence to these type of interventions, and it is necessary to search for new strategies in the treatment of these pathologies [ 11 , 12 ]. Thus, due to the role of gut microbiota alterations in the development of NAFLD and obesity, the administration of prebiotics or probiotics are feasible therapies in the management of these diseases, and the combination of both, namely synbiotics, may potentiate the efficacy of the intervention [ 13 , 14 ]. In fact, the flavonoid quercetin has been reported to counteract NAFLD in in vivo models through a possible prebiotic effect, besides its antioxidant and anti-inflammatory properties [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%